Metabolomic analysis of the impact of red ginseng on equine physiology - Kwak, Young Beom; Stambler, Ilia; Yoo, Hye Hyun; Yoon, Jungho (Frontiers in Veterinary Science, 2024)
IntroductionRed ginseng (RG), a traditional herbal remedy, has garnered attention owing to its diverse health benefits resulting from its complex composition. However, extensive research is needed to substantiate the efficacy of RG and understand the underlying mechanisms supporting these benefits. This study aimed to identify potential biomarkers and investigate the impact of RG on related metabolic pathways in horse plasma using liquid chromatography–mass spectrometry (LC–MS)-based metabolomics.MethodsTen horses were divided into control and RG groups, with the latter administered RG at a dose of 600 mg⋅kg−1⋅day−1 for 3 weeks. Subsequently, the plasma samples were collected and analyzed using LC–MS. Multivariate statistical analysis, volcano plots, and feature-based molecular networking were employed.ResultsThe analysis identified 16 metabolites that substantially decreased and 21 metabolites that substantially increased following RG consumption. Among the identified metabolites were oleanolic acid, ursolic acid, and ginsenoside Rb1, which are known for their antioxidant and anti-inflammatory properties, as well as lipid species that influence sphingolipid and glycerophospholipid metabolism. Additionally, potential biomarkers, including major RG components, demonstrated distinct group clustering in principal component analysis and partial least squares-discriminant analysis, indicating their utility in assessing the physiological effects of RG consumption.DiscussionThis study contributes to a comprehensive understanding of the effects of RG on health.